Anti-Cholinesterase Activity Of Malaysian Cassia Spp. And Its Bioactive Compound - Nurul Azman, Nurul Amira (2020)
Alzheimer’s disease (AD) has become a major concern worldwide as no has cure yet to be found to treat this disease. AD is classified as neurodegenerative disorder with consistently loss of neurons in the cognitive system. To date, cholinergic hypothesis has become the most successful approach to treat AD by inhibiting the acetylcholinesterase enzyme (AChE). Based on our recent published work on the anti- AChE screening of diverse botanical plant family from Malaysia, plants from Cassia spp. showed promising result in inhibiting AChE at high percentage. This project is the continuous study from the previous research to focus on the potential of several Cassia spp. in inhibiting AChE. Five Cassia species including Cassia timorensis, Cassia grandis, Cassia fistula, Cassia spectabilis, and Cassia alata were screened at 200 ppm for in vitro AChE inhibition assay by using the Ellman’s method